Penerapan Metode Taguchi pada Perancangan Eksperimen Beton Geopolimer Berbasis Abu Layang - anggarini, ufafa; Kosada, Claudia; Sukmana, Ndaru Candra (Universitas Ahmad Dahlan, 2017)
PT Petrokima Gresik produces fly ash from coal burning about 8048,89 tons in 2015. In general, one ton of coal burning can produce around 0.15 to 0.17 tons of fly ash waste. Fly ash waste can be utilized as a mixture where the main elements of fly ash are aluminum and silica, fulfilling criteria as the material having cement and geopolymer properties. Geopolymer preparation can be done by the sol-gel method at low temperature, where the emission of CO2 gas produced is a minimum amount. The problem faced is finding the right composition of geopolymer so that it produces the maximum compressive strength. One way is by designing a Taguchi experiment. The choice of the Taguchi method is based on the advantages of this method that can combine experimental results through controlled factors and optimal levels so it can achieve the maximum compressive strength of geopolymer. This research used 3 levels (-1,0,1) and 4 factors of fly ash, the solid/liquid ratio (SL), the molarity of NaOH (A), Sand/pasta geopolymer ratio (P/PG). Anova test showed significant effect on compressive strength of fly ash, S / L and A with value of 12,27> 2,90; 61,12> 2,90; 19,477> 2,90. While the value for P / PG is 1.92 <2.90 where the value of F-statistic is less than F table which means P / PG does not significantly affect the compressive strength of Geopolymer. With S/N higher is better to know the optimum composition of fly ash, S / L, A and P / PG equal to: 370 gram; 2.33 (70:30); 9 Molar, and 1.5. The prediction of Geopolymer maximum compressive strength with Taguchi method was obtained 18,71 Mpa.Â Keywords: Â Fly ash, Optimation, Taguchi, Geopolymer